2013
DOI: 10.1371/journal.pone.0061838
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chromosomal Errors in Human Preimplantation Embryos with Oligonucleotide DNA Microarray

Abstract: A previous study comparing the performance of different platforms for DNA microarray found that the oligonucleotide (oligo) microarray platform containing 385K isothermal probes had the best performance when evaluating dosage sensitivity, precision, specificity, sensitivity and copy number variations border definition. Although oligo microarray platform has been used in some research fields and clinics, it has not been used for aneuploidy screening in human embryos. The present study was designed to use this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…Recently, Yang et al investigated the aneuploidy formation in human embryos derived from young patients (less than 35 years old) and also found that approximately 40 % of blastocysts were aneuploid [7], a rate which was similar to our previous studies with the same age group [5,10]. In Yang's study, they found that transfer of PGS-selected embryos resulted in a higher implantation rate as compared with transfer of non-PGS embryos, suggesting that PGS is necessary not only for patients of advanced maternal ages, but also for young women [7].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Recently, Yang et al investigated the aneuploidy formation in human embryos derived from young patients (less than 35 years old) and also found that approximately 40 % of blastocysts were aneuploid [7], a rate which was similar to our previous studies with the same age group [5,10]. In Yang's study, they found that transfer of PGS-selected embryos resulted in a higher implantation rate as compared with transfer of non-PGS embryos, suggesting that PGS is necessary not only for patients of advanced maternal ages, but also for young women [7].…”
Section: Discussionsupporting
confidence: 79%
“…An age-related reduced embryo implantation can also be improved by the transfer of selected euploid embryos with PGS [5]. Aneuploid embryos are present in infertile patients at various maternal ages with an increased tendency as maternal ages are increased [5,7,10,20,21]. Embryos from healthy egg donors should have low embryonic aneuploidy rates, but a previous study by Sills et al [18] and our present study indicate that high aneuploidy rates are present in human embryos from donor eggs.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations